2008
DOI: 10.1007/s10764-008-9311-4
|View full text |Cite
|
Sign up to set email alerts
|

Female-directed Male Aggression in Wild Ateles geoffroyi yucatanensis

Abstract: Male spider monkeys direct the majority of their aggression toward adult females, and the aggressive interactions may be a form of sexual coercion. We investigated female-directed male aggression in 2 wild communities of spider monkeys (Ateles geoffroyi yucatanensis) from the Otoch Ma'ax Yetel Kooh Reserve in Yucatan, Mexico to evaluate the sexual coercion hypothesis. The aggression occurred in 2 distinct forms: physical aggression and prolonged noncontact chases. The latter appeared highly ritualized in natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…This flexibility in aggressive behavior might result in a better ability to compete with others. Therefore, it might be especially crucial for male primates, as aggressive behavior might be part of males' reproductive success by, for example, increasing their monopolization potential (Barrett et al 2002;Eaton et al 1981;Fedigan and Baxter, 1984;Link et al 2009;Slater et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This flexibility in aggressive behavior might result in a better ability to compete with others. Therefore, it might be especially crucial for male primates, as aggressive behavior might be part of males' reproductive success by, for example, increasing their monopolization potential (Barrett et al 2002;Eaton et al 1981;Fedigan and Baxter, 1984;Link et al 2009;Slater et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Males might therefore experience especially intense competition over resources and will often be involved in aggressive interactions (Mitchell 1979;chimpanzees, Pan troglodytes: Muller and Mitani 2005;Wilson and Wrangham 2003;rhesus macaques: Reinhardt 1987;Japanese macaques: Alexander and Roth 1971;Eaton et al 1981;grivets, Chlorocebus aethiops: Bramblett 1980). Aggressive interactions also frequently occur between males and females (Abondano and Link 2012;Campbell 2003;Fedigan and Baxter 1984;Link et al 2009;Slater et al 2008Slater et al , 2009Van Roosmalen and Klein 1988). However, male aggression to females does not necessarily reflect competition over food resources and might also be part of male reproductive strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…belzebuth: Klein 1972;Link et al 2009;Symington 1987b;and A. paniscus: van Roosmalen and Klein 1987). Aggression from males to females has been suggested to act as a mechanism of "social control" as part of an indirect form of sexual coercion or as a form of ritualized courtship (Fedigan and Baxter 1984;Slater et al 2008), and is part of the repertoire of cooperative behaviors displayed by male spider monkeys that have been suggested to allow the group's males to obtain long-term reproductive benefits by maintaining the cohesion of the group's range (Symington 1987b).…”
Section: Social Behaviormentioning
confidence: 99%
“…Males tend to have higher rates of affiliative interactions with other males than females do (Fedigan and Baxter 1984;Slater et al 2009), which are probably associated with male philopatry and female dispersal , 2010Shimooka et al 2008;Symington 1987aSymington , 1988. Most studies have found a predominant pattern of male-to-female aggression (Fedigan and Baxter 1984;Link et al 2009;Slater et al 2008). However, female-to-female aggression has also been observed, probably as a response to competition for food resources (Asensio et al 2008), given that females require a higher energetic intake to supply the costs of parental care (Trivers 1972).…”
Section: Introductionmentioning
confidence: 99%